Dietary supplementation of tiger nut alters biochemical parameters relevant to erectile function in l-NAME treated rats. (July 2018) - Olabiyi, Ayodeji A.; Carvalho, Fabiano B.; Bottari, Nathieli B.; Lopes, Thauan F.; da Costa, Pauline; Stefanelo, Naiara; Morsch, Vera M.; Akindahunsi, Afolabi A.; Oboh, Ganiyu; Schetinger, Maria Rosa
Abstract: Tiger nut tubers have been reportedly used for the treatment of erectile dysfunction (ED) in folk medicine without scientific basis. Hence, this study evaluated the effect of tiger nut on erectile dysfunction by assessing biochemical parameters relevant to ED in male rats by nitric oxide synthase (NOS) inhibitor, N ω-nitro-l -arginine methyl ester hydrochloride (l -NAME) treatment. Rats were divided into five groups ( n  = 10) each: Control group;l -NAME plus basal diet;l -NAME plus Sildenafil citrate; diet supplemented processed tiger nut (20%) plusl -NAME;diet supplemented raw tiger nut (20%) plusl -NAME.l -NAME pre-treatment (40 mg/kg/day) lasted for 14 days. Arginase, acetycholinesterase (AChE) and adenosine deaminase (ADA) activities as well as nitric oxide levels (NO) in serum, brain and penile tissue were measured.l -NAME increased the activity of arginase, AChE and ADA and reduced NO levels. However, dietary supplementation with tiger nut caused a reduction on the activities of the above enzymes and up regulated nitric oxide levels when compared to the control group. The effect of tiger nut supplemented diet may be said to prevent alterations of the activities of the enzymes relevant in erectile function. Quercetin was revealed to be the most active component of tiger nut tuber by HPLC finger printing. Graphical abstract: Highlights: Effect of dietary supplementation of tiger nut was investigated inl -NAME treated male rats. Treatment with tiger nut supplemented diet increased nitric oxide levels. A reduction of the activities of adenosine deaminase, acetylcholinesterase and arginase was observed. The major phenolic compound in tiger nut is quercetin.